Does Gross or Net Debt Matter More for Emerging Market Spreads? - Hadzi-Vaskov, Metodij (IMF Working Papers; Working Paper ;, 2016)
Does gross or net debt matter for long-term sovereign spreads in emerging markets? The topic is important for undestanding the borrowing cost implications of public assetliability management decisions (e.g. using assets to lower debt). We investigate this question using data on emerging market economies (EMEs) over the period 1998-2014. We find that both gross debt and assets have a significant impact on long-term sovereign bond spreads in emerging markets, with effects roughly offsetting each other (coefficients of opposite sign and similar magnitude). Hence, net debt seems more appropriate than gross debt when evaluating the impact of indebtedness on spreads. The empirical results suggest that an increase in net debt by 10 percentage points of GDP implies an increase in the spread by 100-120 basis points, and the effect is larger during periods of domestic distress. The key results from this empirical study are quite robust to alternative specifications and subgroups of EMEs.